Controls on Capital Inflows and External Shocks - David, Antonio C. (World Bank, Washington, DC, 2012)
The author attempts to analyze whether price-based controls on capital inflows are successful in insulating economies against external shocks. He presents results from vector auto regressive (VAR) models that indicate that Chile and Colombia, countries that adopted controls on capital inflows, seem to have been relatively well insulated against external disturbances. Subsequently, he uses the auto regressive distributed lag (ARDL) approach to co-integration to isolate the effects of the capital controls on the pass-through of external disturbances to domestic interest rates in those economies. The author concludes that there is evidence that the capital controls allowed for greater policy autonomy.